The impact of preoperative inflammatory indices on retinal vessel density and macular perfusion after anti-VEGF treatment in branch retinal vein occlusion (BRVO) using wide-field SS-OCTA - Rong Hu; Chen Zeng; Hao Cui; Ming Li; Chong Tang; Qi Li (Frontiers in Medicine, 2026)
Background This study aimed to comprehensively explore the macular perfusion and topographic distributions of retinal vessel alterations in branch retinal vein occlusion (BRVO)-affected eyes that had been treated with an anti-vascular endothelial growth factor (anti-VEGF) intravitreal injection for 1 month prior, using swept-source optical coherence tomography angiography (SS-OCTA). Methods Thirty BRVO-affected patients with macular edema (ME) who had received anti-VEGF treatment were included in this observational study. All participants were examined using wide-field SS–OCTA before and 1 month after intravitreal injection. The potential association between preoperative serological inflammatory indices and retinal blood flow was explored, and Changes in parameters before and after anti-vascular endothelial growth factor (anti-VEGF) treatment were analyzed. Results After anti-VEGF treatment, central retinal thickness (CRT) was significantly reduced. The vessel density (VD) of nasal location (NL) in superficial retinal vessels (SRV), macular in choriocapillaris (CC), inferior-temporal location (ITL) and NL in SRV with large vessels removed were significant. The VD of macular and NL in in SRV with large vessels removed exhibited distinct interocular discrepancies between the affected eyes and the contralateral eyes. Serological parameters were closely associated with post-treatment ocular microvascular alterations. Conclusion After intravitreous injection for one month, VD of certain retinal sectors of different retinal layers was significantly changed, especially in SRV, while distinctions in DRV were more easily spotted between the affected eyes and the contralateral eyes. Serological inflammatory indices may serve as potential biomarkers for postoperative alterations in VD.